The Bobo in Singapore : a taste culture. - Koh, Bao Yue. (2010)
Using David Brooks’s (2000) concept of the Bourgeois Bohemian (Bobo), this paper explores the extent that such a group exists in Singapore, and the ways in which this group can be characterized. By analyzing the worldviews, consumption habits and lifestyles of respondents, this paper investigates the existence of a Bobo ethos and taste culture. In the 1990s, as a result of successful industrialization and rising affluence, the Singapore Dream of the Five ‘C’s emerged as an ideal economic status that upwardly mobile middle class members aspire to. The Five ‘C’s refer to the economic and material possessions of ‘Cash’, ‘Credit Card’, ‘Condominium’, ‘Car’, and ‘Country Club’. This paper investigates the Bobo taste culture by considering the generational shifts in perceptions and prioritization of the Five ‘C’s. Three new ‘C’s- ‘Clothes’, ‘Cuisine’ and ‘Culture’- will be proposed to illustrate the lifestyle priorities of the Bobos.